Results of the verbal fluency test among patients suffering from depressive disorders and organic depressive disorders - Talarowska, Monika; Zboralski, Krzysztof; Gałecki, Piotr (Current Problems of Psychiatry, 2012)
Objective: Verbal fluency tests are simple clinical tools to assess the effectiveness of working memory, semantic memory, abstract thinking, and lexical-semantic abilities. The aim of this study is to compare the verbal fluency test (VFT) among patients with depressive disorders and organic depressive disorder and to identify indicators of the correctness of the VFT in both groups. Methods: The study involved 105 people (60 women, 45 men), hospitalized atthe Department of Adult Psychiatry Medical University of Lodz. The subjects were divided into two groups: patients with depressive disorders (DD, n = 70) and patients with organic depressive disorder (ODD, n = 35). The study used verbal fluency test consisting of three parts, each of which lasts 60 seconds. The first two categories (semantic) are animals and sharp objects. In the alphabetic part, the task of the test is to provide as many words beginning with the letter ‘k’. Results: Relevant statistical differences among the examined group were observed: in VFT ‘animals’: DD/ODD: p = 0.005; VFT letter ‘k’: DD/ODD: p < 0.001. In both cases, patients with ZD group scored higher than patients from group ODD. Conclusions: 1.Patients with organic depressive disorders achieved significantly lower results than patients with depressive disorders in VFT. 2.The authors determined the TMT performance indicators differentiating between groups: VFT ‘animals’: DD > 12-24 words; ODD > 10-20 words; VFT ‘sharp objects’: DD > 5-12 words; ODD > 4-10 words; VFT „letter ‘k’: DD > 8-18 words; ODD > 5-14 words.depressive disorders